Sliding mode sensor fault tolerant control structure for induction motor - Mohamed, H.A.F.; Yang, S.S.; Moghavvemi, M. (2008)
This paper proposes a fault tolerant control design that consists of two parts: a nominal performance controller and a fault detection element to provide fault compensating signals to the feedback loop. The nominal controller can have any given structure that satisfies the performance specification. The detection element will operate in parallel with the system until a fault is detected. At this time, the compensation enters the feedback loop; when a sensor failure is detected, the controller structure is augmented by signals from plant model to compensate for the fault. To increase the robustness of the proposed control system, a Lyapunov stability based sliding mode controller is designed and used as the nominal controller is this paper. This work presents simulation results to demonstrate how the proposed model based feedback control structure can be designed to tolerate sensor faults. An induction motor control system is used as a case study for the implementation. The results of the simulation for controlling the speed of the induction motor demonstrate the applicability of the proposed FTCS scheme.